The Newest Hypothesis about Vitiligo: Most of the Suggested Pathogeneses of Vitiligo Can Be Attributed to Lack of One Factor, Zinc-α2-Glycoprotein. (19th June 2012) - Bagherani, Nooshin
Abstract : Zinc- α 2-glycoprotein (ZAG) is a recently identified adipokine, assigned to the chromosome 7q22.1. It is a multidisciplinary protein, which is secreted in various body fluids. The ZAG plays roles in lipolysis, regulation of metabolism, cell proliferation and differentiation, regulation of melanin synthesis, cell adhesion, immunoregulation, and so forth. Vitiligo is the most common depigmenting skin disorder, characterized by acquired, progressive, and circumscribed amelanosis of the skin and hair. It commonly begins in childhood or young adulthood. The pathogenesis of this disorder is uncertain, but it appears to be dependent on the interaction of genetic, immunological, and neurological factors. For the first time, we pointed the probable association between ZAG and vitiligo. Herein, I have described this association in different views. By confirming this association, a surprising progression will occur in the treatment of this prevalent debilitating disease.